Energy and the environment - Ristinen, Robert A. (John Wiley and Sons, 1999)
Energy fundamentals, energy use in an industrial society. The fossil fuels. Heat engines. Renewable energy sourcesI: solar energy. Renewable energy sources II: alternatives. The promise and problems of nuclear energy. Energy conservation...